Effects of Bilingualism on Local Content- Based Printed Advertisement for Products Selling by MSME: A Commercial Onomastic Approach - Ulfatmi Azlan; Edwar Kemal; Song Doojin (Universitas PGRI Sumatera Barat, 2024)
Language development today is driven by the rapid pace of technological advancements and the cultural shifts happening around us. However, there are some business owners, called micro enterprises, still use printed advertisement. They use bilingualism on local content-based printed advertisement to sell their product to customers. This research aimed at to find out the effects of bilingualism on local content-based printed advertisement for product selling by MSMEs. These research questions are what are the effects of bilingualism on local content-based printed advertisement for product selling by MSMEs. This research used descriptive qualitative by using content analysis. Data were collected by using interview method using interview question data collection technique. Interview was conducted by using semi-structured interview. Data were analysed by using content analysis combining the theory from Fishman about code-switching and Commercial Onomastic Approach. The research shows that the bilingual advertisements can effectively reach wider customers; advertisement helps to create a sense of cultural connection with the community; bilingual advertisement makes the products offered by MSMEs more relatable and accessible; bilingual advertisements can enhance the perception of inclusivity and professionalism, and bilingual advertisement can lead to increased product awareness, customer loyalty, and higher sales. This research is expected that the MSMEs could show their ideologies or understanding about bilingualism advertisement and for the government, it could to make policy about bilingualism advertisement for public information. This research was limited into Micro Enterprises of West Sumatera MSMEs in Food and Drink type of business.